2013
DOI: 10.1007/s00210-013-0886-8
|View full text |Cite
|
Sign up to set email alerts
|

Olmesartan decreases IL-1β and TNF-α levels; downregulates MMP-2, MMP-9, COX-2, and RANKL; and upregulates OPG in experimental periodontitis

Abstract: The objective of this study is to investigate the participation of inflammatory and oxidative stress mediators and the effects on the expression of matrix metalloproteinase (MMP)-2, MMP-9, and receptor activator of NF-κB ligand (RANKL)/receptor activator of NF-κB (RANK)/osteoprotegerin (OPG) pathway in the response to treatment with olmesartan, an angiotensin II type 1 receptor blocker. Male Wistar albino rats were randomly divided into five groups of ten rats each: (1) non-ligature with water, (2) ligature wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
27
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 31 publications
3
27
0
1
Order By: Relevance
“…In this study, azilsartan treatment produced some results than previous studies by our group using other antihypertensives. Telmisartan and Olmesartan significantly reduced pro-inflammatory cytokines such as IL-1β and TNF-α, which resulted in significant preservation of bone in periodontal disease [2], [3]. In the periodontium, the activation of IL-1β and TNF-α is known to stimulate the degradation of connective tissue matrix, the activation of osteoclasts, and the resorption of bone [17], [18].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, azilsartan treatment produced some results than previous studies by our group using other antihypertensives. Telmisartan and Olmesartan significantly reduced pro-inflammatory cytokines such as IL-1β and TNF-α, which resulted in significant preservation of bone in periodontal disease [2], [3]. In the periodontium, the activation of IL-1β and TNF-α is known to stimulate the degradation of connective tissue matrix, the activation of osteoclasts, and the resorption of bone [17], [18].…”
Section: Discussionmentioning
confidence: 99%
“…12) In particular, olmesartan (OLME) is an angiotensin II type 1 receptor (AT1) blocker that inhibits levels of tumor necrosis factor (TNF)-α and interleukin (IL)-1β, thereby mediating anti-inflammatory activity. 13) In the present study, the effects of OLME on a MTX-induced gastrointestinal mucositis model established in rats were examined. Animals Albino, male Wistar rats (180-330 g; Bioterio Department of Biophysical and Pharmacology) were maintained in a temperature-and humidity-controlled environment with a 12-h light/dark cycle (lights on at 6 a.m.).…”
mentioning
confidence: 99%
“…46) Additional studies have confirmed the anti-inflammatory activity of OLM in other models of inflammation. 19,31,47) Our results are of importance, given that RA is associated with an increased risk of CVD, and that hypertension is a prevalent risk factor for CVD in patients with RA. Thus, the use of OLM in patients with RA can bring dual benefits, due to the drug's anti-inflammatory and antihypertensive properties.…”
Section: )mentioning
confidence: 73%
“…30) In this study and in other experimental models of inflammation, OLM reduced the expression of COX-2, which could result in tissue protection. 19,31) COX-2 is an enzyme induced in inflammatory processes; it is involved in the synthesis of prostaglandins and inflammatory cytokines, which promote local inflammation and tissue damage. Some authors have suggested that COX-2 expression in the synovial fibroblasts of patients with RA contributes to increased expression of inflammatory cytokines in cartilage matrix.…”
Section: Discussionmentioning
confidence: 99%